2016
DOI: 10.1177/1073274816023004s01
|View full text |Cite
|
Sign up to set email alerts
|

Best Practices in Treatment Selection for Patients with Advanced NSCLC

Abstract: Worldwide, lung cancer is the most prevalent form of cancer, and its non-small-cell subtype constitutes up to 85% of cases. Overall, lung cancer is the most common cause of cancer-related death in the United States for both sexes, and its 5-year survival rate is 17%. It is a heterogeneous disease characterized by a variety of biomarkers and differing histologies. Non-small-cell lung cancer may be squamous or nonsquamous in nature and fueled by a number of oncodrivers. Obtaining sufficient tissue during biopsy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Nonsquamous histology has been shown to be a predictive factor in the use of pemetrexed chemotherapy [ 12 ]. Several clinical trials have demonstrated that pemetrexed, when given as a single agent or combined with a platinum analog, provided survival benefit in patients with nonsquamous NSCLC, but showed only some activity in squamous cell patients [ 7 , 13 , 14 ]. For advanced stage squamous cell NSCLC patients, platinum combined with paclitaxel, docetaxel, gemcitabine or vinorelbine are currently the standard treatment options [ 15 ].…”
Section: Biomarkers Used In Nsclcmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonsquamous histology has been shown to be a predictive factor in the use of pemetrexed chemotherapy [ 12 ]. Several clinical trials have demonstrated that pemetrexed, when given as a single agent or combined with a platinum analog, provided survival benefit in patients with nonsquamous NSCLC, but showed only some activity in squamous cell patients [ 7 , 13 , 14 ]. For advanced stage squamous cell NSCLC patients, platinum combined with paclitaxel, docetaxel, gemcitabine or vinorelbine are currently the standard treatment options [ 15 ].…”
Section: Biomarkers Used In Nsclcmentioning
confidence: 99%
“…Several candidate predictive biomarkers may also potentially be useful to identify patients for emerging targeted therapy approaches. These include RET rearrangements and MET alterations [ 14 , 16 , 20 ]. MET is considered a strong candidate given its response to crizotinib, currently a treatment for ALK - and ROS1 -rearranged lung cancers [ 14 , 25 ], however, MET alterations are uncommon, occurring in approximately 5% of NSCLC.…”
Section: Biomarkers Used In Nsclcmentioning
confidence: 99%
“…In 2015, an estimated 73,330 new lung cancer cases and 61,020 new lung cancer mortalities were reported in China [ 2 ]. Lung cancer is divided into two major histological types: SCLC (small-cell lung cancer) and NSCLC, with the latter accounting for 85% of all lung cancers [ 3 ]. NSCLC includes adenocarcinoma, squamous cell carcinoma, and large cell lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Second-line chemotherapy may include pemetrexed in non-squamous cancer and docetaxel or erlotinib (or both) in all types of NSCLC. NSCLC management has positively evolved from the emergence of immunotherapy, currently positioned as second line therapy [ 18 ]. Antitumor activity, long lasting response and survival increases in advanced NSCLC patients has been demonstrated with the use of anti-PD-1 passive immunotherapy [ 19 ], leading to regulatory approval of an anti-PD-1 drug, nivolumab (Opdivo; Bristol-Myers Squibb) [ 20 ] for the treatment of metastatic squamous non–small-cell lung cancer (NSCLC) in patients who have progressed on a platinum-based chemotherapy.…”
Section: Discussionmentioning
confidence: 99%